Nonalcoholic fatty liver disease burden: Australia, 2019–2030 - Adams, Leon A; Roberts, Stuart K; Strasser, Simone I; Mahady, Suzanne E; Powell, Elizabeth; Estes, Chris; Razavi, Homie; George, Jacob (Journal of gastroenterology and hepatology, 2020)
Background and Aim Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) account for a large and growing proportion of liver disease burden globally. The burden of NAFLD/NASH manifests in increasing levels of advanced liver disease and primary liver cancer in Australia. A Markov model was used to forecast NAFLD burden in Australia through 2030. Methods A model was used to estimate fibrosis progression, primary liver cancer, and liver deaths among the Australian NAFLD population, with changes in incident NAFLD cases based on long‐term trends for changes in the prevalence of obesity. Published estimates and surveillance data were applied to build and validate the model projections, including surveillance data for the incidence of liver cancer. Results Prevalent NAFLD cases were projected to increase 25% from the current burden (5 551 000 [4 748 000–6 306 000] cases in 2019) to 7 024 000 [5 838 000–7 886 000] cases in 2030. The projected increase in the number of NASH cases (40%) was greater than that of NAFLD cases. Incident cases of advanced liver disease are projected to increase up to 85% by 2030, and incident NAFLD liver deaths are estimated to increase 85% from 1900 (1100–3300) deaths in 2019 to 3500 (2100–6100) deaths in 2030. Conclusions Restraining growth of the obese and diabetic populations, along with potential therapeutic options, will be essential for mitigating disease burden.